Welcoming the new, revisiting the old: a brief glance at cytopathology reporting systems for lung, pancreas, and thyroid - Rita Luis; Balamurugan Thirunavukkarasu; Deepali Jain; Sule Canberk (Korean Society of Pathologists & the Korean Society for Cytopathology, 2024)
This review addresses new reporting systems for lung and pancreatobiliary cytopathology as well as the most recent edition of The Bethesda Reporting System for Thyroid Cytopathology. The review spans past, present, and future aspects within the context of the intricate interplay between traditional morphological assessments and cutting-edge molecular diagnostics. For lung and pancreas, the authors discuss the evolution of reporting systems, emphasizing the bridge between past directives and more recent collaborative efforts of the International Academy of Cytology and the World Health Organization in shaping universal reporting systems. The review offers a brief overview of the structure of these novel systems, highlighting their strengths and pinpointing areas that require further refinement. For thyroid, the authors primarily focus on the third edition of The Bethesda System for Reporting Thyroid Cytopathology, also considering the two preceding editions. This review serves as an invaluable resource for cytopathologists, offering a panoramic view of the evolving landscape of cytopathology reporting and pointing out the integrative role of the cytopathologist in an era of rapid diagnostic and therapeutic advancements.